Kajian Arsitektur Neo Vernakular pada Bangunan di Taman Krida Budaya Kota Malang - Dharma, Wahyu Nursila; Farida Murti; Tohar, Ibrahim (Universitas Medan Area, 2025)
Indonesia is a country with various ethnicities and cultures. Each region of Indonesia has its own culture and uniqueness. As modern times become more modern, many local wisdoms and characteristics are starting to disappear. One way to ensure that local wisdom remains is by implementing neo vernacular architecture. Neo vernacular architecture is a form of applying architectural components to buildings in the form of shapes, structures and/or elements that are not in physical form such as concepts, thought patterns and spatial planning, which has the aim of using local components created from community culture to be futuristic and modern without reducing existing traditional elements. Research was carried out to look for the characteristics of Neo Vernacular Architecture in the cultural park area. The method used is qualitative description, by conducting literature studies and field observations. The place used as the object is the Krida Budaya Park in Lowokwaru District, Malang City. From the observations that have been made, it was found that Taman Krida Budaya applies the concept of neo vernacular architecture in several parts of the building, both in the main building and in supporting buildings.